Analysis of higher-order thinking skills of science students at Madrasyah Tsanawiyah Muslim Nahdatul Ulama during the Covid-19 Pandemic - Adinda Dwi Saputri Sugino; Erman Erman (Jurnal Pijar Mipa, 2022)
This study aims to describe the higher-order thinking skills of Muslim students of Madrasyah Tsanawiyah Muslim Nahdatul Ulama Sidoarjo Indonesia during the Covid-19 pandemic. The type of research is descriptive analysis with a quantitative approach by analyzing students' higher-order thinking skills on the structure and function of plant tissues, vibrations and waves, and the circulatory system. The subjects of this study were one science teacher and 36 students in the eighth grade. The research instrument consisted of a HOTS test sheet, questionnaire, and interview sheet. The interview sheet consists of 9 questions analyzed with NVIVO 12 software and a test containing five questions on each material, including the HOTS indicator. The data analysis technique used is descriptive statistics. The results showed a decrease in students' HOTS abilities during the pandemic. It is marked by the achievement of average scores and students' abilities in the creative component, which tended to be low in the three materials measured. The decline in students' HOTS abilities before and during the pandemic occurred in the three indicators with the most significant reduction, namely the creating indicator, followed by analysis and evaluation. During the pandemic, the implementation of HOTS-based learning takes place with various forms of adaptation. The difference in implementing HOTS-based learning lies in the frequency of implementing HOTS-based learning for each material and learning model used, and the learning steps. The results of this study can be used as input for science teachers to implement HOTS-based learning during the pandemic.